“It is not your body. It is not your right”: visual arguments of the Argentinean pro-life movement on Instagram - Tarullo, Raquel (2022)
This paper studies the arguments and mobilization strategies used by the pro-life movement in Argentina on Instagram during the debates about the legalization of abortion in 2018. To analyse these strategies, we compiled a corpus, which includes the images published over eleven months by the two accounts of the pro-life associations with most followers on Instagram. The analysis combines two methods: visual content analysis and multimodal critical discourse analysis. Results show that these accounts used different mobilization repertoires (Unidad provida aimed at mobilizing the supporters even at a local level, while Unidos por las dos vidas wanted to persuade the followers, impact them, and stigmatize women). Nevertheless, both accounts converged in the use of the historical argumentation and persuasion strategies of the anti-abortion movement in Argentina, adapting them to the specific affordances of Instagram, without substantially modifying their content. In addition, on occasions, they also constructed visual and textual counterarguments opposed to those of the pro-choice movement.